A Redox‐Active Nickel Complex that Acts as an Electron Mediator in Photochemical Giese Reactions - van Leeuwen, Thomas; Buzzetti, Luca; Perego, Luca Alessandro; Melchiorre, Paolo (Angewandte Chemie International Edition, 2019)
We report a simple protocol for the photochemical Giese addition of C(sp3)‐centered radicals to a variety of electron‐poor olefins. The chemistry does not require external photoredox catalysts. Instead, it harnesses the excited‐state reactivity of 4‐alkyl‐1,4‐dihydropyridines (4‐alkyl‐DHPs) to generate alkyl radicals. Crucial for reactivity is the use of a catalytic amount of Ni(bpy)32+ (bpy=2,2′‐bipyridyl), which acts as an electron mediator to facilitate the redox processes involving fleeting and highly reactive intermediates. A time to get, and a time to lose electrons: Electron mediators can alleviate limitations associated with the photochemistry of excited‐state intermediates, including short lifetimes and low electron transfer rates. The ability of a nickel complex to act as an electron shuttle assists the excited‐state reactivity of dihydropyridines 1 to enable a photochemical Giese addition of C(sp3)‐centered radicals to electron‐poor olefins.